The Effect of Quality Service and Operational Standard Procedures to Operational Performance at CV Pabrik Tahu Sumedang - Fahreza, Rizky Raihan; Hananto, Djoko; Polinar, Mark Anthony N. (Transpublika Publisher, 2025)
In the highly competitive food and beverage industry, operational efficiency is key to business sustainability; however, fluctuations in tofu consumption in East Jakarta as well as CV Pabrik Tahu Sumedang's production indicate challenges influenced by service quality and suboptimal implementation of Standard Operating Procedure (SOP). The objective of this research is to examine how Quality Service and Standard Operating Procedures (SOP) impact operational performance of CV Pabrik Tahu Sumedang. Operational performance is a crucial aspect of the food and beverage industry that affects efficiency, effectiveness, and customer satisfaction. The study utilises a quantitative method, gathering data through surveys given to CV Pabrik Tahu Sumedang employees. An analysis of the data was conducted using multiple linear regression to explore the correlation between Quality Service and SOP as independent variables, and Operational Performance as the dependent variable. The findings demonstrate that Quality Service positively and significantly influences Operational Performance. Similarly, the proper implementation of SOPs significantly improves operational efficiency and effectiveness. Furthermore, simultaneous analysis shows that Quality Service and SOPs together contribute significantly to enhancing Operational Performance. These findings confirm that optimising service quality and consistently implementing SOPs can enhance the factory’s competitiveness and productivity. The originality of this research lies in analyzing the effect of service quality and standard operating procedures on operational performance in the context of the traditional food industry, which still lacks scientific exploration. This approach provides a new contribution in the context of operational management in small-medium enterprises based on local products.